SUN-LB17 The Association of Growth Hormone Treatment in Children With Short Stature With Idiopathic Scoliosis - Nam, Hyo-Kyoung (J Endocr Soc, 2020)
Objectives: Adolescent idiopathic scoliosis (AIS) is the most common form of scoliosis, which occurs usually in the periods of growth spurts and puberty changes. The spinal curve progression in AIS is related to growth, skeletal maturity and sexual maturity. Growth hormone treatment has been used to improve final adult height by increasing growth velocity in children with short stature. Therefore, AIS is expected to occur more frequently in children treated with growth hormone. The aim of this study was to investigate the relationship between AIS and growth hormone treatment in short children. Methods: A total 115 subjects aged 2.1 to 16.9 years who had been treated with growth hormone because of growth hormone deficiency (n=83), idiopathic short stature (n=16) and small for gestational age (n=16) were included. Their medical records were reviewed retrospectively. The scoliosis angle of each subject was measured on the standing frontal radiograph according to the Cobb method. A curve with a Cobb angle of 10 degrees or more is defined scoliosis. Follow up Cobb angle were measured after 1-year of growth hormone treatment. Results: Cobb angle has been increased after 1-year growth hormone treatment (6.1±3.1 vs. 6.9±3.4, P=0.024). The change of Cobb angle was correlated with serum insulin like growth factor-1 level at baseline (r=0.274, P=0.003) and after 1-year of growth hormone treatment (r=0.220, P=0.020). There was no significant correlation between the change of Cobb angle and growth velocity. The prevalence of AIS has been increased after 1-yrear of growth hormone treatment (11.3% vs. 19.1%, P=0.009). Conclusion: Growth hormone treatment in children with short stature seems to be associated with occurring and worsening of AIS.